Intergenerational transmission of child abuse in Colombia: an analysis of gendered effects - Camargo, Esperanza (Revista Española de Investigación Criminológica, 2018)
A broad range of research literature has studied patterns of intergenerational violence. However, scant research has looked at how those patterns are gendered. This study examines gendered patterns of intergenerational transmission of violence and looks at how gender relates to intimate partner violence and child physical abuse over time. I used a 2015 dataset of 12.915 interviews with Colombian heterosexual couples who were married or living together at the time of the interview. Using factor analysis and structural equation modeling (SEM), I found, consistent with previous studies, that parental history of child abuse was a predictor of physical child abuse; this is consistent with previous studies. Experiencing physical punishment by one’s parents was a stronger predictor of the use of physical punishment on one’s own children in adulthood than being an observer of partner violence between one’s parents. However, the female observer of parental male-to-female partner abuse was more likely also to be a victim of intimate partner abuse in adulthood, and experiencing physical punishment by one’s parents also predicts a male’s physical victimization. Overall, the results support social learning theory and liberal feminist theory, that gender roles, gender inequality, and power structure are learned, passed from one generation to the next, and perpetuated by family relationships.